The Use of Electronic Medical Records - Simbolon, Pomarida; Ginting, Arjuna; Boris, Jev (Global Health Science Group, 2024)
Electronic medical records are concrete evidence of the increasingly developed world of health. After paper-based medical records, the Ministry of Health requested that all health services in Indonesia be able to use electronic medical records. The use of electronic medical records is one indicator of providing good performance for health workers. The use of electronic medical records (EMR) greatly influences the achievement of health workers' work results. The aim of the research is to identify the use of electronic medical records in the Inpatient Room at Santa Elisabeth Hospital Medan in 2023. This type of research is descriptive. The sample in the study consisted of 40 respondents using a proportional stratified random sampling technique. Data collection was carried out using a questionnaire. Data were analyzed using univariate analysis. The research results showed that 33 people (82.5%) were satisfied with the use of electronic medical records. It is hoped that Santa Elisabeth Hospital Medan can improve the electronic medical record (sphaira) application and carry out socialization every 2 months if there is an application update so that the use of electronic medical records is even better.